Acoustic Space - Schafer, R. (Circuit)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractStarting from McLuhan’s concept of acoustic space, the author discusses how the World Soundscape which he undertook at Simon Fraser University in 1970 set out to put this notion into practice by studying how the soundscape influences all aspects of people’s lives. In the extract published here, the author finds that the sphere is the geometric shape which best describes acoustic space, and discusses the sybolism of the sphere – and of sound – in the cultures of the world.